Measuring inflation expectations in Finland: a survey data approach - Mika Kuismanen; Mikko Spolander (Bank of Finland, 1994)
This paper gives a short overview of how inflation expectations are measured in Finland and considers the possibilities of using such data to predict actual inflation. In Finland, there are three regularly published surveys, which include questions on ex post perceptions and/or ex ante expectations of the direction of change in the general price level or in the inflation rate.They are conducted by Statistics Finland (TK), the Confederation of Finnish Industry and Employers (TT) and the newspaper Helsingin Sanomat (HS). In the TK data expectations match realized rates of inflation quite well but the time series is too short.In the TT data the time series is long enough but the match between expectations and realized rates is poor.In HS data the match is quite good and the time series covers more than one business cycle. According to the correlation analysis, it seems that the TK data and the HS data could be used to form some kind of estimate of the future rate of consumer price inflation.By contrast, the TT data is probably better for predicting wholesale, producer or export price inflation. Although the HS data seems to offer us the best modelling possibilities, it is not very useful as a single exogenous variable in explaining realized rates of inflation.The small number of observations alone limits the use of advanced econometric methods and several exogenous variables.With the accumulation of more observations over time, however, we will be able to expand the model and the use of alternative data.For particular, the TK data seems quite promising.
URN:NBN:fi:bof-20140807455
Keywords: 330